Cultural Competency in Local Government Cemetery Management. (2nd January 2021) - Zavattaro, Staci M.
Abstract : Local government cemetery management is an unexplored area of public administration, and this paper begins to tackle that gap by exploring the role of cultural competency in the role. Based on a content analysis of interviews with 35 municipal cemetery managers throughout the U.S., I find cultural competence manifests in several ways: racial segregation even in death; intersectional identities; and funeral economics. The paper brings to light the ways in which cemetery managers must confront, understand, and tackle cultural differences in life, death, and beyond.